Management Challenges for Multiple-Species Boreal Forests - Anne Sophie Crépin (Fondazione Eni Enrico Mattei (FEEM), 2003)
Recent research in natural sciences shows that boreal forests' dynamics are much more complex than what many models traditionally used in forestry economics reflect. This essay analyses some challenges of accounting for such complexity. When forest owners continuously harvest several species, more than one harvesting strategy can be optimal. Which one it is depends on the forest's initial state. For some initial states, two different strategies may yield the same welfare. If whole stand harvesting of one tree species is preferred, the optimal period between each harvesting occasions depends on other species' dynamics.
Keywords: Q23; Q26; Q29; 330; Multiple Steady States; Forestry; Non-Convexities; Moose; Wald; Forstwirtschaft; Nordeuropa